Dynamics of Change in the Criminal Case Plea Bargaining System: New York City, 1800-1890 - Mirsky, Chester L. ([Verlag nicht ermittelbar], 1996)
This study analyzes the ascendancy of a single form of dispute processing--the guilty plea--in New York City's principal indictment court, and its connection to law enforcement, judges, and lawyers. A major component of the study is a statistical analysis of data presented in the Minute Book of Court of General Sessions and maintained at the New York City Archives. A second data source is the New York City district attorney's case files, also maintained at the New York City Archives. Part 1, District Attorney Case File Data, contains a sample of cases throughout the century taken from the district attorney's files. Variables cover charge filed, method of arrest, nature of testimony, presence of the lawyers, role of police, private prosecutor, and magistrate, and demographic information about the defendant and victim. Part 2, Lawyer Data, records the frequency of the appearance of individual lawyers, the charges in the cases in which they appeared, the lawyering activities they undertook, and the method of case disposition. Part 3, Minute Book Data, reflects the workday of the Court of General Sessions, including the number of cases processed in court on any given day, the number of defendants tried, the details of charges, joinder, witness examinations, outcome and sentence, and the number pleading guilty. Part 4, Cases Tried Data, not only records cases tried but also includes the top count, legal representation, result, and sentence, and for cases pleading guilty contains the top count charged, top count accepted, and sentence imposed. District Attorney Reference Data, Part 5, contains cases in which copies of the district attorney's papers were not found. These cases occurred on the same day as cases for which copies of the district attorney's papers were recorded. This data served as a control group for the District Attorney Case File Data.